Use of programming aids in undergraduate courses - Peixoto, A.; Glória, A.; Silva, J. L.; Pinto-Albuquerque, M.; Brandão, T.; Nunes, L. (5th International Computer Programming Education Conference (ICPEC 2024), 2024)
The use of external tips and applications to help with programming assignments, by novice programmers, is a double-edged sword, it can help by showing examples of problem-solving strategies, but it can also prevent learning because recognizing a good solution is not the same skill as creating one. A study was conducted during the 2superscriptnd semester of 23/24 in the course of Object Oriented Programming to help understand the impact of the programming aids in learning. The main questions that drove this study were: Which type(s) of assistance do students use when learning to program? When / where do they use it? Does it affect grades? Results, even though with a relatively small sample, seem to indicate that students who used aids have a perception of improved learning when using advice from Colleagues, Copilot-style tools, and Large Language Models. Results of correlating average grades with the usage of tools suggest that experience in using these tools is key for its successful use, but, contrary to students' perceptions, learning gains are marginal in the end result.